HSCT FOR ACUTE MYELOID LEUKEMIA - Silla, Lúcia; Arantes, Adriano; Astigarraga, Claudia; Barroso, Karine Sampaio Nunes; Beltrame, Miriam Perlingeiro; Bettarello, Gustavo; Campregher, Paulo; Duarte, Fernando Barroso; Funke, Vaneuza Araújo Moreira; Furtado, Felipe Magalhães; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION